Effects of the “Free of COVID-19” educational program on teenagers’ preventive social skills - Lora-Loza, Miryam (2021)
Objective: To determine the effects of the “Free of COVID-19” educational program on the preventive social skills of teenagers treated at a provincial hospital in Peru. Materials and methods: An explanatory, pre-experimental, longitudinal and prospective research with a pretest and posttest intact group design. The population consisted of 40 male and female teenagers aged between 13 and 19, who were treated at the Tayabamba provincial hospital. The inclusion criteria were a) teenagers aged between 13 and 19, b) teenagers with complete medical records and c) teenagers treated at the Tayabamba provincial hospital. The variables (before and after the program) were the preventive social skills and their dimensions: assertiveness, communication, self-esteem and decision-making. The “Free of COVID-19” educational program was implemented with a pretest and a posttest. A questionnaire made up of four dimensions and 27 questions was administered for assessing the preventive social skills. A non-parametric analysis of longitudinal data was used for a sample of subjects who were evaluated twice during the course of the study. Results: Before the implementation of the “Free of COVID-19” educational program, the teenagers’ preventive social skills were, in general terms, fair (55.00 %) and, after the program, good (80.00 %). Their assertiveness was fair (45.00 %) before the program and improved to good (75.00 %) after the program. Their communication was fair (70.00 %) before the program and good (85.00 %) afterwards. Their decision-making was good (50.00 %) before the program and also good (90.00 %) after the implementation of the program. Conclusions: The preventive social skills of teenagers treated at the Tayabamba provincial hospital, as well as their assertiveness, communication, self-esteem and decision-making, significantly improved with the implementation of the “Free of COVID-19” educational program.